Analisis Faktor Geopolitik di Balik Ambisi Maritim Indonesia Dalam Lingkup Regional dan Global - Risa Amalia Kurniawati; Nurul Khotimah; Gunawan Santoso (Yayasan Aya Sophia Indonesia, 2024)
This article analyzes the geopolitical factors driving Indonesia's maritime ambitions in the context of great power competition in the Indo-Pacific region. With its strategic position as an archipelagic state, Indonesia is important in maintaining regional stability, capitalizing on its blue economy potential, and managing challenges such as territorial disputes and maritime security threats. Using a descriptive qualitative approach, this research explores Indonesia's maritime policy by analyzing official documents, geopolitical theory, and regional and global dynamics. The results show that Indonesia's maritime strategy relies on regional diplomacy, infrastructure improvement, naval modernization, and sustainable environmental management. However, cross-sector coordination, external challenges, and environmental sustainability issues are the main obstacles. This article offers policy recommendations to support Indonesia's vision as a world maritime axis, including strengthening diplomacy, infrastructure investment, defense modernization, and integrated environmental policies.